Haemoglobin status and predictors of anaemia among pregnant women in Mpigi, Uganda - Ononge, Sam; Campbell, Oona; Mirembe, Florence (BMC Research Notes, 2014)
Anaemia in pregnancy is a major public health problem especially in the low-income countries where it is highly prevalent. There has been no recent study in Uganda about the factors associated with anaemia in pregnancy. We aimed to assess the current haemoglobin (Hb) status and factors associated with anaemia (Hb < 11.0 g/dl) in pregnant women in Mpigi, Uganda. Methods: We assessed Hb levels of 2436 pregnant women at 28+ weeks of gestation at six health facilities, who were approached to participate in a stepped-wedge cluster-randomised trial of antenatal distribution of misoprostol (for self-administration after home birth or when oxytocin is not available). Women were administered a questionnaire and their baseline blood haemoglobin was examined using portable HemoCueR Hb 301 system. Predictors of anaemia were estimated using linear and logistic regression analysis.
Keywords: Haemoglobin; Anaemia; Pregnancy